(untitled) (GEON Journal (Management, Organizations and Business), 2015)
In this paper the relationship between the external client Water and Sewerage Company and feedback it has with the client described , considering the Colombian technical standard ISO 9001: 2008 specifically paragraphs 7.2.3 Customer Communication, 8.2.1 customer Satisfaction, performing a diagnostic entity , analyzing customer perception through the survey of user satisfaction survey and external clients in the development of work , allowing identify situations that hinder communication with the client, determine the means of most used between the client and the company and propose actions to improve the communication entity .